Ethoxyresorufin-O-deethylase (EROD) inducing potency of polycyclic aromatic hydrocarbons (PAHs) in avian hepatocyte cultures: Investigations of the ability of an in vitro bioassay to predict the toxic potency of PAHs. - Jeffery, Richard William Paul. (Université d'Ottawa / University of Ottawa, 2001)
Eighteen polycyclic aromatic hydrocarbons (PAHs) and 2,3,7,8-tetrachlorodibenzo-pdioxin (TCDD) were examined for their potencies to induce ethoxyresorufin-O-deethylase (EROD) activity in primary cultures of White Leghorn chicken (Gallus domesticus), Pekin duck (Anas platyrhynchos), and Greater Scaup (Aythya marila) embryo hepatocytes. Of the 18 PAHs, only eight induced EROD activity. In chicken hepatocytes the rank order of potency of the eight EROD inducing PAHs was BkF ≥ DahA > Ind > BaA ≥ BghiP ≥ Chr ≥ BaP > BNT. A log-log plot of the ECthr plotted against the LD50 (LD50 data from Brunstrom et al., 1991) for BkF, DahA, BaA, and BNT resulted in a good correlation (r2 = 0.898) between EROD-inducing potency and in ovo lethality. The regression line was used to predict LD50 values for Ind, Chr, and BaP. Although the regression line overestimated the LD50 values, the estimated values appear to be within one order of magnitude of their approximate LD50. The rank order of induction potency of the eight EROD-inducing PAHs in duck and scaup hepatocytes was BkF ≥ DahA > BaP ≥ Ind > BghiP ≥ Chr ≥ BaA > BNT, and BkF ≥ DahA > BaP ≥ Ind > BaA ≥ BghiP > Chr, respectively. Among species, there was no clear overall trend in relative sensitivity to EROD induction by individual PAHs. The EROD inducing potency of zebra mussel (Dreissena polymorpha) extracts was investigated in hepatocytes of all three species. The rank order of sensitivity to the extracts was chicken > duck ≥ scaup. While TCDD and several PCBs induce porphyrin accumulation in chicken embryo hepatocytes, none of the PAHs elicited this response. Regardless of the lack of porphyrinogenic effects, the EROD data suggests that primary cultures of avian embryo hepatocytes maybe a useful model for predicting the in ovo toxic potencies of PAHs in avian species.